The Effect Of Compensation And Organizational Culture On Employee Performance With Work Motivation As An Intervening Variable At PT Kimia Farma Apotek Purwokerto Business Unit - Muchtar Habib; Nurul Qomariah; Abadi Sanosra (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study analyzes the effects of compensation and organizational culture on employee performance, with work motivation as an intervening variable, at PT Kimia Farma Apotek Purwokerto Business Unit. A quantitative associative approach was used. The population consisted of 34 employees, and all were included through saturated sampling. Data were collected through questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that compensation and organizational culture have positive and significant effects on both work motivation and employee performance. Work motivation also positively affects employee performance and significantly mediates the effects of compensation and organizational culture on performance. These findings indicate that strengthening organizational culture and improving compensation systems can enhance employee performance both directly and indirectly through higher work motivation.